Opini Masyarakat tentang Bisnis Kuliner Online di Kota Berastagi Kabupaten Karo Provinsi Sumatera Utara - Bobby Rahman; Binur Pretty Napitupulu (Politeknik Pariwisata Medan, 2022)
Technological progress is so fast that it can be felt by entrepreneurs, especially culinary businesses in Indonesia, with this technological advancement which is widely used by culinary business actors, such as those in Berastagi City, Karo Regency, where this area is a tourist destination that is visited by many tourists. tourists both from outside and from within the country, the variety of attractions offered as well as the culinary delights. Online media is one of the media for culinary business actors in selling a variety of culinary delights that are marketed which are usually used as promotional tools to market these various culinary delights. The type used in this research is a type of quantitative descriptive research. Where the results of the enthusiastic research of the community in using online media in culinary orders are increasing and continue to increase. This online culinary business makes it easy for people to buy the food they want without having to leave their homes or surroundings. The process of ordering and delivery as well as payment is very efficient, fast and practical, making the online culinary business in Berastagi City, Karo Regency even better